Wildfire smoke impacts respiratory health more than fine particles from other sources: observational evidence from Southern California - Rosana Aguilera (Nature Communications, 2021)
Recent toxicological studies suggest that wildfire particulate matter may be more toxic than equal doses of ambient PM2.5. Here, the authors show that even for similar exposure levels, PM2.5 from wildfires is considerably more dangerous for respiratory health at the population level.